2013
DOI: 10.1055/s-0032-1328461
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Sesquiterpenoid Derivatives from Ferula ferulaeoides

Abstract: Three new sesquiterpenoid derivatives 1, 2, and 3 were isolated from Ferula ferulaeoides. To confirm the structure, compound 2 was also synthesized via a condensation reaction between compound 1 and 2,2-dimethoxypropane. The structures of these three compounds were elucidated by means of spectroscopic and chemical methods. Their antibacterial activity against drug-resistant Staphylococcus aureus strains were evaluated with MIC values in the range of 0.5-128 µg/mL. Compounds 1 and 3 were capable of inhibiting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…UV absorptions at l max 275.0 and 238.5 nm supported the presence of ac haracteristic 2,4dihydroxyacetophenone moiety.T he 1D-NMR data (Table 1)s uggested that compound 13 had askeleton consisting of adihydroxyphenyl ethyl ketone connected to a farnesyl moiety.T his skeleton was the same as that of 9,p reviously isolated from the same plant [29]. In comparison with 9,c ompound 13 had an additional AcO group instead of aOHgroup at C(8) in 9.Therefore,compound 13 was the 8-AcO-and 9-OHsubstituted derivative of dshamirone (5).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…UV absorptions at l max 275.0 and 238.5 nm supported the presence of ac haracteristic 2,4dihydroxyacetophenone moiety.T he 1D-NMR data (Table 1)s uggested that compound 13 had askeleton consisting of adihydroxyphenyl ethyl ketone connected to a farnesyl moiety.T his skeleton was the same as that of 9,p reviously isolated from the same plant [29]. In comparison with 9,c ompound 13 had an additional AcO group instead of aOHgroup at C(8) in 9.Therefore,compound 13 was the 8-AcO-and 9-OHsubstituted derivative of dshamirone (5).…”
mentioning
confidence: 94%
“…It has been reported to contain aseries of sesquiterpenes and derivatives [22 -27].Inour screening for new antibacterial agents,a ne xtract of F. ferulioides was found to possess antibacterial activity against ap anel of bacteria. Apart from ap esticidally active sesquiterpene,guaiol [28], our preliminary research resulted in the isolation of two new antibacterial sesquiterpenoids that inhibit efflux pumps of drug-resistant Staphylococcus aureus strains [29]. In an extensive phytochemical investigation, seven new sesquiterpenoid derivatives,together with 21 known sesquiterpenoid derivatives were isolated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,12 In addition, the extracts have been reported to have antimicrobial, anthelmintic, anticonvulsant, antispasmodic, antihyperglycemic, antihyperlipidemic, and antioxidant activities. [13][14][15][16][17][18]…”
Section: Introductionmentioning
confidence: 99%
“…The Awei from F. sinkiangensis and F. fukanensis are recognized in the Chinese Pharmacopoeia as Traditional Chinese Medicines. Phytochemical research has revealed that derivatives of sesquiterpene coumarins are responsible for diverse bioactivities exhibited by plants of the Ferula genus, including antitumor [16], anti-immune inflammatory [15,17], antibacterial [18,19], and disinsection [20,21] activity. However, there are few reports of the genus Ferula with respect to a potential therapeutic effect on AD by targeting the inhibition of over-activation of microglial cells.…”
Section: Introductionmentioning
confidence: 99%